Matrix Support: interface between Specialty Dental Centers and primary oral health care in Brazil - Thaislaine Gonçalves Martins Santos; Livia Fernandes Probst; Rafaela da Silveira Pinto; Edilson José Zafalon; Alessandro Diogo De-Carli (BMC, 2024)
Abstract Background Matrix Support (MS) is a strategy that can be used to improve integration between Primary Health Care (PHC) and other levels of care. Objective The aim of this study was to investigate the association between MS carried out in Brazilian Dental Specialty Centers (CEOs) (secondary level of oral health care) and aspects of the integrated work process with PHC, as well as contextual variables. Methods A quantitative cross-sectional study was conducted using data from the Program for Quality Improvement and Access to CEOs (PMAQ-CEO). Secondary data from the External Evaluation of the second cycle of PMAQ-CEO were analyzed, including contextual variables obtained from sources such as the Unified Health System (SUS) and official research institutions. Descriptive analyses were performed, and four multiple models were adjusted to investigate the association between the variables. Results The results showed that about half of the CEOs did not carry out therapeutic projects developed with the oral health teams of PHC. It was found that the lack of therapeutic projects developed with the teams was associated with the lack of discussion of complex cases by the team, lack of discussion of individual therapeutic project, absence of joint continuing education activities, lack of construction and discussion of clinical protocols, and lack of belief in the importance of planning and periodic evaluation. The results suggest that the articulation between PHC and secondary oral health care still presents weaknesses within the scope of SUS. Comprehensive care needs to be strengthened, requiring greater intervention from management. Conclusion It was concluded that the individual factors of CEOs, related to the work process, have a greater influence on the lack of integration with oral health teams of PHC, compared to the contextual variables of municipalities.